Lesbian Identities In Audiovisual Productions: Research and analyses of lesbian characters and their plots - Unanue Cuesta, María Concepción (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The proposal of the research is to review and analyse the role of the media as constructors of social imaginaries, and to do so, we will analyse the power of the audiovisual industry to create and re-create stereotypes about lesbians, and as generators of a social imaginary, we will also analyse lesbian plots and characters, through which direct messages are sent to society in general, but also to lesbians. Finally, after conducting discussion groups and focus groups with lesbians who have participated in the research, we present some conclusions.